KORELASI SELF EFFICACY DENGAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS VII SMPN 42 PEKANBARU PADA MASA PANDEMI COVID-19 - Nurul Destia Anggraini Ardi; Wan Syafi’i; Riki Apriyandi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to determine the correlation of self-efficacy with cognitive learning outcomes in science for class VII students of SMP N 42 Pekanbaru during the Covid-19 pandemic. In order to achieve this goal, quantitative research was carried out in the form of correlation research and descriptive research design. The variables observed in this study were self-efficacy (self-confidence) and student science cognitive learning outcomes which were carried out in November 2021-January 2022. The instruments used were validation sheets, self-efficacy questionnaires and test instruments. The data source comes from primary data, namely the results of closed questionnaire data from self-efficacy and the results of students' cognitive tests in the form of objective questions on natural science material classification of living things and open interviews. The results of the study showed that there was a significant correlation between self-efficacy (X) and cognitive learning outcomes in science (Y) in the moderate category in science learning class VII SMP Negeri 42 Pekanbaru during the Covid-19 pandemic in the 2021/2022 academic year. self-efficacy affects science cognitive learning outcomes by 28.39% and the remaining 71.61% is influenced by other factors not determined in this study. So based on the results of this study it would be very good if students were able to increase self-efficacy to support improving their learning outcomesKey Words: Self Efficacy; Science Cognitive Learning Outcomes; Covid-19 pandemic